Evaluation of antimicrobial peptide LL-37 for treatment of Staphylococcus aureus biofilm on titanium plate. Issue 44 (5th November 2021) - Wei, Jiantong; Cao, Xuepeng; Qian, Jun; Liu, Zhixia; Wang, Xulong; Su, Qinliuye; Wang, Yongpin; Xie, Ruimin; Li, Xiang
Abstract : Abstract: The antimicrobial peptide LL-37 belongs to the cathelicidin family and is one of the few human bactericidal peptides with potent antistaphylococcal activity. Staphylococcus aureus is one of the main infection bacteria in orthopedic implant therapy. Biofilm formation after bacterial infection brings more and more severe test for clinical antiinfection treatment. However, there are few studies on LL-37 in S. aureus infection of prosthesis. In this work, addition to research the antibacterial activity and the inhibitory effect on bacterial adhesion of LL-37, an in vitro model of S. aureus biofilm formation on titanium alloy surface was established to observe the inhibitory effect of LL-37. The results showed that LL-37 has a strong antibacterial effect on S. aureus in vitro, and the minimum inhibitory concentration (MIC) is about 0.62 μΜ. Moreover, LL-37 has significant impact on the adhesion of S. aureus when the concentration ≥0.16 μM and significant anti-staphylococcal biofilm effects on static biofilm models at the concentration of 0.31 to 10 μM. Additionally, LL-37 at 5 μM had a significant destructive effect on S. aureus biofilm ( P  < .05) that formed on the titanium alloy surface. This study further confirmed the role of LL-37 in the process of S. aureus infection, including antimicrobial activities, inhibition of bacterial adhesion, and inhibition of mature biofilm. LL-37 can significantly destroy the stable biofilm structure on the titanium alloy surface in vitro, which may provide a new way for refractory infection caused by S. aureus in titanium alloy prosthesis infection.